Effects of mother related factors on perinatal outcomes-a study of mothers seeking antenatal care at public and non-public health facilities in Kisii County, Kenya - Micah Matiang'i; Simon Karanja; Peter Wanzala; Kenneth Ngure; Albino Luciani (AOSIS, 2017)
The study sought to determine clientlevel and facility-level factors that affect perinatal outcomes among women attending comparable public (government owned) and non-public health facilities (non-government owned) in Kisii County-Kenya in the context of free maternity care. A total of 365 pregnant mothers recruited in 4 health facilities during their ANC visit and followed up to 2 weeks post-delivery but only 287 attended all follow-up visits. Study subjects were recruited proportionate to number of deliveries each of the facilities had conducted in the preceding 6 months. The dependent variable was perinatal outcome; independent variables were demographic and clinical factors. Analysis was done using χ2, logistic regression, paired t and McNemar's tests. Maternal BMI and a mother's parity were statistically correlated with perinatal outcome (χ2= 8.900, d.f =3, P=0.031 and (χ2= 13.232, d.f =4, P=0.039) respectively. Mothers with 1 parity were 4.5 times more likely to have normal perinatal outcomes (OR =4.5, 95% CI 2.25-14.29, P=0.012). There was a significant relationship between a mother's knowledge of pregnancy-related issues and the baby's weight (t=-67.8 d.f. 213 P<0.001). Mothers' knowledge on pregnancy issues and spousal involvement influences perinatal outcomes. Dietary Diversity Score (DDS) of a mother does not have a direct influence on the outcome of a pregnancy. There is need to focus on maternal factors that affect perinatal outcomes besides free maternity care.